Recreio escolar: concepções e formas de vivências de alunos do Ensino Fundamental I, na Escola Municipal Nazaré Gomes Torres - SILVA, Vânia Maria Brito da (2019)
This work was developed with the title "School Recreation: conceptions and forms of experiences of Elementary School I students, in the Nazaré Gomes Torres Municipal School", because it is an instigating and not very visible topic in educational research, since students do not have mentioned school of a moment of leisure in the playground. As a result, this moment of recreation becomes a problem, because students instead of playing normally, are led to run, shout, jump and even fight at that time, without there being a pedagogical direction guided by the managers, technicians and teachers who alter the vision of the playground with aggression, irritation, running, disrespect and conflict. The general objective is to analyze the school playground at the Municipal School Maria de Nazaré Gomes Torres, the students' conceptions and their ways of living this moment of the school pedagogical process. And specific: discuss theoretical - conceptual notions about school play; to identify how some legal prescriptions of education demarcate the importance of school play; and finally to understand the perceptions of some subjects inserted in the educational-school process about the recreation. The work is justified since the researches with the subject are scarce, there is no work of pedagogical intervention for the moment of recess, neither directed by the SEMED, nor School, nor is it contemplated in the Rules of the Municipal Schools of Castanhal, and neither in the PPP of the researched school. The research has a qualitative approach. It is bibliographical and field. We have worked with the authors: Andrade (2018), Bardin (2011), Bichara (2006), Ferreira (2018), Ferreiro (1985), Kishimoto (2010), Lins, (2018), Oliveira 2018), Rosa (2014), Saviane (2018), Severino (2007), Souza (2009), Souza (2013), and Wurdig (2018). The results of the research indicate that in relation to the conceptions and experiences of the school in the playground, documents such as the Municipal School Rules of Castanhal, as well as the LDBN do not make direct reference to the context of the school playground in their texts, only give indications of the nature and spaces of the same in the school environment, and so little the PPP of the school. Therefore, it is concluded that it is necessary that both institutions and school subjects seek to reflect and study the subject so that they can propose a moment of recreation as an important part of the learning relationships experienced in the school.